Membangun Budaya Literasi Anak Usia Dini dalam Keluarga - Ria Nurhayati (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2019)
The lack of interest in reading in Indonesia is one of the factors of the weak literacy index in Indonesia. Based on the survey, Indonesia is the 62nd country out of 70 countries in literacy level. This is the author's background for writing articles about building a culture of early childhood literacy. Literacy culture is not only developed at school but at home parents should start developing a literacy culture for early childhood. This research was conducted by analyzing various centralized sources such as books and scientific articles to get a formulation on how to build early childhood literacy at home. The results show that various activities at home can be designed to build a literacy culture for early childhood. The activeness of parents plays a very important role in efforts to build a culture of early childhood literacy.